Identifikasi Indigenous Knowledge Suku Sasak Sebagai Upaya Pengembangan Pembelajaran Biologi Untuk Mendukung Konsep Merdeka Belajar - Muchsin, Adnan; Sriyati, Siti; Solihat, Rini (Jurnal Paedagogy, 2023)
This study aims to identify indigenous knowledge or local wisdom of Sasak Tribe in Lombok Island, which has the potential of integration into Biology learning, especially in Phase E, to support Merdeka Belajar policy. This research used a qualitative descriptive method, in which description was used to analyze and interpret data. The data were collected through interviews, documentation, and literary studies to be analyzed using triangulation technique, coding, and interpretation. The results of this study showed that the indigenous knowledge of the Sasak Tribe had the potential of integrated into Biology learning, especially in Phase E, namely Biodiversity substance with the local wisdom of Kemaleq, Loang Gali, Mangku Gawar, Loh Dewa, and Loh Makem, Bau Nyale, Weaving Sesek, Medicinal Plants and Bale Tani/Ketapahan, Ecosystem material with the local wisdom of Kemaleq, Loang Gali, Mangku Gawar, Loh Dewa and Loh Makem, Bau Nyale and Ngaro/Nenggala. The concept of Waste and Natural Materials relates to the local wisdom of Belulut and Ngaro/Nenggala. In contrast, the concept of Biotechnology Innovation related to the local wisdom of Poteng Rekat. From this arranged framework, it is hoped to be utilized in developing teaching materials, modules, worksheets, questions and tasks development, and other instruments in Biology subject.